Effects of Aging and Anatomic Location on Gene Expression in Human Retina - Cai, Hui; Fields, Mark A.; Hoshino, Risa; Del Priore, Lucian V. (Frontiers in Aging Neuroscience, 2012)
Objective: To determine the effects of age and topographic location on gene expression in human neural retina. Methods: Macular and peripheral neural retina RNA were isolated from human donor eyes for DNA microarray and quantitative RT-PCR analyses. Results: Total RNA integrity from human donors was preserved. Hierarchical clustering analysis demonstrates that the gene expression profiles of young, old, macula and peripheral retina cluster into four distinct groups. Genes which are highly expressed in macular, peripheral, young or old retina were identified, including inhibitors of Wnt Signaling Pathway (DKK1, FZD10 and SFRP2) which are preferably expressed in the periphery. Conclusions: The transcriptome of the human retina is affected by age and topographic location. Wnt pathway inhibitors in the periphery may maintain peripheral retinal cells in an undifferentiated state. Understanding the effects of age and topographic location on gene expression may lead to the development of new therapeutic interventions for age-related eye diseases.